A institucionalização do Turismo como curso universitário: décadas de 1960 e 1970 - Celeste Filho, Macioniro [UNESP] (My University, 2012)
This text is about the appearing of Tourism graduation courses in Brazilian colleges. To this, the creation of the curricula at the Federal Board of Education was studied and the emergence of Tourism graduation courses offered by private universities. The creation of the first Tourism course in a public university – at the beginning of the 70’s at the School of Communications and Art of São Paulo University – is emphasized.

Este texto trata do surgimento dos cursos superiores de Turismo no Brasil. Para tanto, estudou-se a criação dos currículos sobre o tema no Conselho Federal de Educação e o surgimento dos cursos superiores de Turismo em faculdades privadas. Destaca-se a criação do primeiro curso de Turismo numa universidade pública brasileira no início da década de 1970, na Escola de Comunicações e Artes da Universidade de São Paulo.
The institutionalization of tourism as university study: decades of 1960 and 1970
Keywords: Tourism graduation; School of Communication and Arts; US; Graduação em Turismo; Escola de Comunicação e Artes; USP